Co-movements of Shanghai and New York Stock prices by time-varying regressions - Gregory C. Chow; Changjiang Liu; Linlin Niu (Bank of Finland, Institute for Economies in Transition (BOFIT), 2011)
We estimate a time-varying regression model to study the relationship between returns in the Shanghai and New York stock markets, with possible inclusion of lagged returns. The parameters of the regressions reveal that the effect of the current stock return for New York on that for Shanghai steadily increases after the 1997 Asian financial crisis and turns significantly and persistently positive after 2002, when China entered WTO. The effect of the current return for Shanghai on New York also becomes significantly positive and increasing after 2002. The upward trend has been interrupted during the recent global financial crisis, but reaches the level of about 0.4 to 0.5 in 2010 for both markets. Our results show that China's stock market has become more and more integrated into the world market in the past twenty years, with interruptions occurring during the recent global economic downturn.
URN:NBN:fi:bof-201408071947
Keywords: 330